Partisipasi Pria Dalam Keluarga Berencana Di Kecamatan Jetis Kabupaten Bantul - Iman Budisantoso, Saptono (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2009)
Background: Male participation in Family Planning in Indonesia was still low. Indonesian Demographic Health Survey 2002 showed 4.4% man participation in family planning acceptors and only 4.3% in Bantul. The aim of this research was to know factors related man participation in family planning program, in Jetis Sub District, Bantul, 2008.Method: The study is an explanatory research with a survey research method using a cross sectional approach. The samples of this study were 100 participants of reproductive age from 9.074 of reproductive age chosen by multistage random sampling. Data analyses of this study were univariate, bivariate by chi square and multivariate by logistic regression for quantitative method and Focus Group Discussion (FGD) used for qualitative method.Result: The result of this study showed there were relation between knowledge of man participation in family planning, attitude for man participation in family planning, perceived of man participation in family planning, wife attitude for man participation in family planning, wife practice for man participation in family planning, friend attitude for man participation in family planning, friend practice for man participation in family planning with man participation in family planning. Variables of education and service access for man participation in family planning not related with man participation in family planning. The obstacle in social value related with man participation in family planning, like family planning was forbidden,family planning was a women area, a boy has a higher value than a girl, and domain of areluctant factor. Wife practice for man participation in family planning was the most related Independent variable.Keywords: participation, man, family, planning